IN VIVO EFFECT OF TREMA GUINEENSIS LEAVES EXTRACTS ON IRON STATUS DURING INFLAMMATION AND PAIN - YEBOUE KOFFI FRANCOIS, KOUAKOU; MARIUS, LEBRI; YAO YVES, KOUAME (International Journal of Phytomedicine, 2025)
The purpose of this study was to evaluate the effect of raw extracts of Trema guineensis leaves on the iron status during inflammation and pain. Inflammation was induced by carrageenan in the plantar cushion of the right hind leg of the wistar rat. The pain was induced by acetic acid in the abdominal contortion model in wistar rats. The iron concentration during the inflammatory process and pain was determined by an atomic absorption spectrophotometer. The quantitative assay of the biomarkers transferrin and ferritin was carried out by the immunoturbidimetric method with the latex particles sensitized by the specific antibodies using a biochemical analyzer called Cobas C-311. The results show that serum iron (25.88 ± 0.52 or 27.51 ± 2.25 µmol/L) and transferrin (1.98 ± 0.02 or 1.79 ± 0.06 g/L) concentrations increased significantly (p < 0.05) when animals with inflammation or pain were treated with the aqueous extract, compared to the control group (NaCl + carrageenan or NaCl + acetic acid). The same observation was made in the hydroethanolic extract whose serum iron and transferrin concentrations were 32.82 ± 0.23 µmol/L and 2.02 ± 0.04 g/L during inflammation and next 30.12 ± 1.58 µmol/L and 1.93 ± 0.09 g/L during pain, respectively. In contrast to the above, ferritin concentrations decreased significantly (p < 0.05) when animals in both states were treated with both Trema guineensis extracts, compared to control (NaCl + carrageenan or NaCl + acetic acid). We can conclude that the input of Trema guineensis leaves corrected the disruption of iron status caused by inflammation and pain.